1983
DOI: 10.1136/jnnp.46.9.804
|View full text |Cite
|
Sign up to set email alerts
|

Apraxia in deep cerebral lesions.

Abstract: SUMMARY In a series of 50 patients with cerebrovascular lesions (demonstrated with CT scan), seven patients had lesions located in the basal ganglia and/or thalamus. All these seven patients were apractic. Ideomotor apraxia was present in all patients; five also had constructional apraxia, and one had bucco-facial apraxia. None of the patients had utilisation apraxia. These observations indicated that apraxia is not only a "high cerebral (cortical) function", but may depend also on the integrity of subcortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Several adults with thalamic lesions and apraxia have been reported (Cappa and Vignolo 1979, Alexander and LoVerme 1980, Agostoni et al 1983, Graff-Radford et al 1984, DeRenzi et al 1986, Della Salla et al 1992, Shuren et al 1994, most in association with an aphasia. Nadeau et al (1994) suggest that the praxis deficit seen with thalamic lesions is a reflection of a declarative memory deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Several adults with thalamic lesions and apraxia have been reported (Cappa and Vignolo 1979, Alexander and LoVerme 1980, Agostoni et al 1983, Graff-Radford et al 1984, DeRenzi et al 1986, Della Salla et al 1992, Shuren et al 1994, most in association with an aphasia. Nadeau et al (1994) suggest that the praxis deficit seen with thalamic lesions is a reflection of a declarative memory deficit.…”
Section: Discussionmentioning
confidence: 99%
“…In 1983 Agostoni et al published seven cases of patients with lesions of the basal ganglia developing ideomotor limb apraxia, more studies on apraxia in patients with subcortical lesions were reported soon thereafter [1,32]. Moreover, in 1991 Shelton [43] found ideomotor apraxia in three of nine patients with Huntington's disease (HD), a rare hereditary,devastating neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 97%
“…The first cases of ideomotor limb apraxia in patients with diseases that were subcortical in origin were reported in the 1980s, when case reports were published on apraxic patients with vascular subcortical dementia, PD and normal-pressure hydrocephalus [13,14] . Similarly, apraxia in HD, where predominantly subcortical structures are damaged, was first identified by Shelton in 1991, after which 2 further similar studies followed [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%